2016
DOI: 10.1097/md.0000000000005466
|View full text |Cite|
|
Sign up to set email alerts
|

Models predicting the risks of six life-threatening morbidities and bile leakage in 14,970 hepatectomy patients registered in the National Clinical Database of Japan

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 35 publications
3
50
1
Order By: Relevance
“…The characteristic complications of this surgery, such as pulmonary embolism and arrhythmia, require special attention as they can be life-threatening. Although a recent report 23 observed cardiac events in only 0⋅9 per cent of patients after hepatectomy, these events, including pulmonary embolism and arrhythmia, occurred in seven of the 37 patients in the study. Furthermore, cardiac events occurred, all in patients who had not required VVB or CPB, contrary to expectations; however, considering the procedures used, it is not hard to imagine that the risk of cardiac events is extremely high, whether or not extracorporeal circulation was used.…”
Section: Discussioncontrasting
confidence: 55%
“…The characteristic complications of this surgery, such as pulmonary embolism and arrhythmia, require special attention as they can be life-threatening. Although a recent report 23 observed cardiac events in only 0⋅9 per cent of patients after hepatectomy, these events, including pulmonary embolism and arrhythmia, occurred in seven of the 37 patients in the study. Furthermore, cardiac events occurred, all in patients who had not required VVB or CPB, contrary to expectations; however, considering the procedures used, it is not hard to imagine that the risk of cardiac events is extremely high, whether or not extracorporeal circulation was used.…”
Section: Discussioncontrasting
confidence: 55%
“…There are fewer large‐scale reviews focusing on the influences of obesity on liver surgery than on gastrointestinal surgery. The main diseases studied are hepatocellular carcinoma and liver metastasis of colorectal cancer, but there are reviews actually targeting all hepatic disorders . Table shows a summary of past studies on the effects of obesity on outcomes of liver surgery.…”
Section: Liver Surgerymentioning
confidence: 99%
“…Our group conducted a large‐scale review to examine the impacts of obesity on hepatic resection and found that obesity (BMI > 30) prolonged operative time by approximately 50 min as compared to surgery on non‐obese patients undergoing hepatectomy of more than one segment apart from the lateral segment (n = 14 903) . In addition, Yokoo et al, studying a similar surgical group, reported BMI > 30 to potentially be a risk factor for blood transfusion and BMI > 35 to be a risk factor for unplanned intubation (n = 14 970). In a similar report, Langella et al noted that resection time, blood loss, and rate of pulmonary complications tended to rise if BMI > 30, and that obesity may negatively influence all three of these factors.…”
Section: Liver Surgerymentioning
confidence: 99%
“…Better or worse outcomes can be detected by the monitoring report. Furthermore, we are proceeding with papers on complications related to each of the eight operative methods for the evaluation of medical standards using data from 2011 and 2012 . To assure collection of high‐quality data, the Japanese Society of Gastroenterological Surgery (JSGS) have started data verification activities for a gastroenterological session in NCD in 2016.…”
Section: Introductionmentioning
confidence: 99%